Gender, management and transition in central and eastern Europe - Afanassieva, Marianne; Metcalfe, Beverley (Women in management, 2005)
Introducing gender, management and transition researchThe majority of studies on economic and political reform in central and eastern Europe(CEE) have failed to consider how men and women are differently affected bytransition from command to market economies (Grapard, 1997; Degtiar, 2000). Thisfailure is likely to have serious consequences for the economic and social well being ofwomen who seem to have borne greater costs of the restructuring. This special issuecontributes to this under explored debate. This special issue complements the previousissue of Women in Management Review (Vol. 20 No.